FOLIAR MICROMORPHOLOGY OF LIPPIA JAVANICA (BURM.F) SPRENG - Asowata-Ayodele, Abiola Mojisola; Afolayan, Anthony Jide; Otunola, Gloria Aderonke (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Lippia javanica (Burm.F.) Spreng is an aromatic indigenous South African plant with culinary and medicinal values.This study investigated the foliar morphology and elemental composition of the plant because not much data concerning theanatomical and micro-morphological features can be found in literatureMaterials and Methods: Fresh leaves of the plant were investigated using light and scanning electron microscopy (SEM). Theelemental composition of the leaf was determined by energy dispersive X-ray spectroscopy.Results: The leaves of L. javanica were amphitrichomic while the stomata distribution was amphistomatic. These stomata weremore or less randomly distributed over the epidermis lying almost close to each other and were fewer in number in between the veinsand over the finer veins. The major constituents of crystals found in the plant were Ca, Na, S, Al, P, Cl, K, Mg and Fe. The presenceof long glandular trichomes on the leaf surfaces of the plant could indicate secretory sites where secondary metabolites are produced.Conclusion: Secretions from the glandular trichomes and the presence of these elements, which are vital in maintaining good health,are probably responsible for the culinary and medicinal properties of L. javanica.